Rainbow Options with MS–VAR process - Gankhuu, Battulga (Mongolian Mathematical Journal, 2023)
This paper presents pricing and hedging methods for rainbow options and lookback options under Markov-Switching Vector Autoregressive (MS–VAR) process. Here we assumed that a regime–switching process is generated by a homogeneous Markov process. An advantage of our model is it depends on economic variables and simple as compared with previous existing papers.